2012
DOI: 10.5762/kais.2012.13.9.4065
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of topical EMLA Cream for venipuncture on Patients' Pain and Anxiety

Abstract: The purpose of this study was to examine the effect of topical EMLA Cream on venipuncture related pain and anxiety of surgery patient from oct. 27 to nov, 13, 2011, EMLA Cream was applied to the experimental group(n=40) 1hour before the procedure, but was not applied to the control group (n=37). The collected data were analyzed with the SPSS WIN 15.0 program. The percentage, mean and standard deviation were figured statistic, χ 2-test, t-test, ANOVA, Correlation analysis were performed. Consequently, Pain in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
5
1
Order By: Relevance
“…In contrast to the above findings, a previous study [23] found that a 2% lidocaine intradermal injection or 10% lidocaine spraying had no effect on pain or anxiety reduction in patients with arteriovenous aneurysm undergoing blood dialysis. Nevertheless, 35.3% of their study participants showed satisfaction with the spraying method, and 58.8% wished to reuse it.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In contrast to the above findings, a previous study [23] found that a 2% lidocaine intradermal injection or 10% lidocaine spraying had no effect on pain or anxiety reduction in patients with arteriovenous aneurysm undergoing blood dialysis. Nevertheless, 35.3% of their study participants showed satisfaction with the spraying method, and 58.8% wished to reuse it.…”
Section: Discussioncontrasting
confidence: 75%
“…In the previous study, the spraying frequency was set as three times per patient and no effect of spraying frequency was found on the extent of surface anesthesia. Therefore, in this research 10% lidocaine was sprayed three consecutive times on the venipuncture area [23].…”
Section: Experimental Processmentioning
confidence: 99%
“…The same prior study suggested putting on a tegaderm after applying EMLA cream to maximize skin absorption of EMLA cream. However, we only applied EMLA cream to reduce the inconvenience of multiple manipulations [3]. After at least 30 minutes, the cream was removed with gauzes and vital signs (blood pressure and pulse) were measured.…”
Section: Data Collectionmentioning
confidence: 99%
“…Based on prior research of the efficacy of EMLA cream at least 30 minutes after cannulation [3], we applied 2 mm thickness of EMLA cream on an expected intravenous injection site of subjects at least 30 minutes before IV injection. The same prior study suggested putting on a tegaderm after applying EMLA cream to maximize skin absorption of EMLA cream.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation